Industrial revolution 4.0 - evidence of theoretical perspective "science become a direct production force" of Karl Marx - Binh, Nguyen Quang; Son, Bui Vu Hong (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
By applying dialectical materialism to the study of social fields (especially social production), K.Marx predicted: when scientific content is increasing in the level of workers and work tools make fixed capital transform to a certain degree, it will become a direct production force. The evolution of the current industrial revolution 4.0 is a compelling evidence for the genius prediction of K.Marx 160 years ago. Clarifying the point that “science becomes a direct production force” of K.Marx in the context of industrial revolution 4.0 is especially important to demonstrate some solutions to promote the effectiveness of science and technology for the development of production forces in Vietnam today. Code: 18042401